Highly efficient circular holes added a-Si: H grating coupler with metal mirror for 3D optical interconnects - Kang, JoonHyun; Kuno, Yuki; Ito, Kazuto; Hayashi, Yusuke; Arai, Shigehisa; Han, Il-Ki; Amemiya, Tomohiro; Nishiyama, Nobuhiko; Suzuki, Junichi (2016 21ST OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE (OECC) HELD JOINTLY WITH 2016 INTERNATIONAL CONFERENCE ON PHOTONICS IN SWITCHING (PS), 2016)
A monolithically fabricated apodized a-Si: H grating coupler with metal mirror was demonstrated The minimum groove length for the apodized grating was more than 100 nm and measured coupling efficiency was 70%.